ANALISIS SOCIAL MEDIA MARKETING DAN BRAND AWARENESS TERHADAP IMPULSIVE BUYING - Mariah Mariah; Asri Pertiwi (JURNAL LENTERA BISNIS, 2022)
This study aims to analyze social media marketing ads and brand awareness of impulse buying in the MSME sector for home-based ethnic clothing products at Ethnicnesia Online Stores. This research uses quantitative research with 94 respondents who are consumers who usually buy ethnic clothes made of woven fabrics. The sampling method was purposive sampling. This study uses quantitative research methods by conducting surveys, the results of validity and reliability tests using SPSS v 20.0, and hypothesis testing is carried out using simple linear regression method.Keywords: social media marketing, brand awareness, impulsive buying.